2015
DOI: 10.4172/1948-5948.1000189
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptides: Biosynthesis and Applications

Abstract: Microbial surfactants are amphiphilic molecules. They possess a strong tendency to reduce the interfacial tension among compounds. Biosurfactants possess diverse chemical structures and are nontoxic and hence are biodegradable. They have many applications in bioremediation, enhanced oil recovery, pharmaceutical and in food industry. In addition, biosurfactants have antifungal, antibacterial and antiviral properties. They are also found to have many therapeutic applications which as a result are very helpful fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…Kiran et al [35] studied on the functional groups of rhamnolipids from the sponges and Aspergillus sp. Walaa et al, [16] determined the free -OH stretching at 3430 cm -1 , the C-H stretching vibrations of CH2 and CH3 groups at 2938 cm -1 , C=O from ester and carboxylic groups that were observed at 1739 cm -1 and 1629 cm -1 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kiran et al [35] studied on the functional groups of rhamnolipids from the sponges and Aspergillus sp. Walaa et al, [16] determined the free -OH stretching at 3430 cm -1 , the C-H stretching vibrations of CH2 and CH3 groups at 2938 cm -1 , C=O from ester and carboxylic groups that were observed at 1739 cm -1 and 1629 cm -1 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several strains from this genus are known to produce a wide variety of biocontrol metabolites, including ribosomally synthesized antimicrobial peptides (bacteriocins) as well as non-ribosomally synthesized peptides (NRPs) and polyketides (PKs) (Zhao and Kuipers 2016). NRPS, PKS or hybrid NPRS/PKS genes from Bacillus strains usually encode lipopeptide compounds mainly known for their antifungal properties such as iturins, fengycins and bacillomycin (Walia and Cameotra 2015). Lou et al (2014) confirmed the contribution of lipopeptides bacillomycin L and surfactin, produced by Bacillus subtilis 916, in controlling sheath blight in rice plants caused by Rhizoctonia solani.…”
Section: Discussionmentioning
confidence: 99%
“…(5) After reduction of the methanol phase, a defatting step had to be performed using n-hexane as well as the following devices: Ultrasonic bath (Sonorex Super RK 100 H, Bandelin electronic GmbH & Co. KG, Germany), separator funnel (500 mL, Lenz Laborglas GmbH & Co. KG, Germany), Buchner funnel (Duran Buchner funnel, Merck, Germany) with cellulose filter (Whatman cellulose filter, Merck, Germany) and a filter funnel (POR 5, DWK Life Sciences GmbH, Germany). (6) The preparative HPLC was performed with a JASCO system. For separation, a C18 column was used (Eurospher EI 100-10 C18 Column 250 × 32 mm, Knauer Wissenschaftliche Geräte GmbH, Germany).…”
Section: Process Units For Jagaricin Purificationmentioning
confidence: 99%
“…Owing to this characteristic, lipopeptides have various physicochemical properties such as emulsification/de‐emulsification, dispersing, foaming, viscosity reducing, solubilizing and mobilizing agents, and pore‐forming capacity [ 1 ]. Additionally, lipopeptides show diverse biological activities such as antimicrobial, antiviral, hemolytic, and insecticidal effects [ 1 , 5 , 6 ]. With properties such as eco‐friendliness, specificity, low toxicity, stability in varying environmental conditions, and chemical diversity, some microbial biosurfactants stand the chance of replacing synthetic surfactants in industrial applications soon [ 7 ].…”
Section: Introductionmentioning
confidence: 99%